Dating of young (<1 Ma) tephras: Using U‐Pb (zircon) and (U‐Th[‐Sm])/He (zircon, apatite, magnetite) chronometers to unravel the eruption age of a tephra in the Woodlark Rift of Papua New Guinea. (16th April 2020) - Österle, Jürgen E.; Stockli, Daniel F.; Seward, Diane; Little, Timothy A.
Abstract: The dating of volcanic tephras forms a critical cornerstone of chronostratigraphy and is paramount for the resolution of the geological timescale. (U‐Th[‐Sm])/He dating is an emerging tool in Quaternary tephrochronology and ideally suited to date tephras <1 Ma. We present zircon, magnetite and apatite (U‐Th[‐Sm])/He combined with zircon U‐Pb data for a Pleistocene tephra in syn‐rift strata of the Woodlark Rift in Papua New Guinea. The results reveal a young He age mode ( 0.5 to 0.8 Ma), consistent with an autocrystic zircon U‐Pb crystallisation age of 0.8 ± 0.1 Ma, as well as a broad range of older (U‐Th[‐Sm])/He ( 1.6 to 10.2 Ma) and U‐Pb ( 4.4 to 107 Ma) ages. These data demonstrate the potential of integrated U‐Pb and (U‐Th[‐Sm])/He multi‐method chronometry for dating the youngest coherent age mode, detecting contaminant grains and evaluating the isotopic systematics of these techniques.